Thermodynamics for engineers - Wong, Kau-Fui Vincent (Mechanical engineering series (Boca Raton, Fla.), 2012)
Praise for the First Edition from Students: "It is a great thermodynamics text I loved it!-Mathew Walters "The book is comprehensive and easy to understand. I love the real world examples and problems, they make you feel like you are learning something very practical."--Craig Paxton"I would recommend the book to friends."-Faure J. Malo-Molina"The clear diction, as well as informative illustrations and diagrams, help convey the material clearly to the reader."-Paul C. Start"An inspiring and effective tool for any aspiring scientist or engineer. Definitely the best book on Classical Thermodynamics out."-Seth Marini